COVID-19 severity in Sub-Saharan Africa and the systematic use of anti-malarial drugs - Fonte Galindo, Luis; Ginori Gilkes, MarÃa; GarcÃa Menéndez, Gissel; Sarmiento RodrÃguez, MarÃa Elena; Acosta DomÃnguez, Armando (Revista Cubana de Medicina Tropical, 2021)
As it is a manuscript to be published in the Reflection and Debate section, no abstract is applicable.